MutTCPdb: a comprehensive database for genomic variants of a tropical country neglected disease—tropical calcific pancreatitis. (24th July 2018) - Singh, Garima; Bhat, Basharat; Jayadev, M S K; Madhusudhan, Ch; Singh, Ashutosh
Abstract: Tropical calcific pancreatitis (TCP) is a juvenile, non-alcoholic form of chronic pancreatitis with its exclusive presence in tropical regions associated with the low economic status. TCP initiates in the childhood itself and then proliferates silently. mutTCPdb is a manually curated and comprehensive disease specific single nucleotide variant (SNV) database. Extensive search strategies were employed to create a repository while SNV information was collected from published articles. Several existing databases such as the dbSNP, Uniprot, miRTarBase2.0, HGNC, PFAM, KEGG, PROSITE, MINT, BIOGRID 3.4 and Ensemble Genome Browser 87 were queried to collect information specific to the gene. mutTCPdb is running on the XAMPP web server with MYSQL database in the backend for data storage and management. Currently, the mutTCPdb enlists 100 variants of all 11 genes identified in TCP, out of which 45 are non-synonymous (missense, nonsense, deletions and insertions), 46 are present in non-coding regions (UTRs, promoter region and introns) and 9 are synonymous variants. The database is highly curated for disease-specific gene variants and provides complete information on function, transcript information, pathways, interactions, miRNAs and PubMed references along with remarks. It is an informative portal for clinicians and researchers for a better understanding of the disease, as it may help in identifying novel targets and diagnostic markers, hence, can be a source to improve the strategies for TCP management. Database URL: http://lms.snu.edu.in/mutTCPDB/index.php